Revision of the genus Tanycypris (Ostracoda, Cypricercinae) with the description of Tanycypris alfonsi n. sp., and an identification key to the genus - Nagler, Christina; Geist, Juergen; Matzke-Karasz, Renate (Zootaxa, 2014)
Specimens of a new species of the non-marine ostracod genus, Tanycypris Triebel, 1959 were found in samples from water plant containers, displayed in a greenhouse of the botanical garden in Munich, Germany. Beside the ubiquitous species Cypridopsis vidua O.F. Müller, 1776, the samples contained four alien species of the subfamily Cypricercinae, namely Chlamydotheca arcuata Sars, 1901, Strandesia bicuspis Claus, 1892, Tanycypris centa Chang et al., 2012, and Tanycypris alfonsi n. sp.. The genus Tanycypris has mainly been reported (native) from Asia, and (invasive) from Italian rice fields.        The Cypricercinae unite all species possessing a Triebel loop, a character of the caudal rami attachment. The subfamily is split into the tribes Cypricercini McKenzie, 1971, Bradleystrandesiini Savatenalinton & Martens, 2009 and Nealecypridini Savatenalinton & Martens, 2009, the latter of which comprises the genera Tanycypris Triebel, 1959, Astenocypris G.W. Müller, 1912, Diaphanocypris Würdig & Pinto, 1990 and Nealecypris Savatenalinton & Martens, 2009.        During the process of describing the new species, a number of taxonomic uncertainties were detected within the genus Tanycypris, leading to a revision of the nine species currently ascribed to it: Tanycypris camaguinensis (Tressler, 1937), Tanycypris centa Chang et al., 2012 Tanycypris clavigera (G.W. Müller, 1898) (now: Nealecypris clavigera nov. comb.), Tanycypris madagascarensis (G.W. Müller, 1898), Tanycypris marina (Hartmann, 1965) (now: Dolerocypris marina nov. comb.), Tanycypris pedroensis (Tressler, 1950) (now: Diaphanocypris pedroensis nov. comb.), Tanycypris pellucida (Klie, 1932), Tanycypris siamensis Savatenalinton & Martens, 2009a, and Tanycypris telavivensis (Krampner, 1928) (now: Herpetocypris telavivensis). An identification key has been developed to the species of the genus Tanycypris.